Tibiotalar Arthrodesis Conversion to Total Ankle Arthroplasty - Pellegrini, Manuel J. (JBJS Essent Surg Tech, 2016)
INTRODUCTION: Although conversion of the painful ankle arthrodesis to total ankle arthroplasty remains controversial, this surgical modality has satisfactorily expanded the treatment armamentarium for addressing this pathology. INDICATIONS & CONTRAINDICATIONS: STEP 1: PREOPERATIVE PREPARATION AND SURGICAL PLANNING: Preoperative preparation and planning is similar to that for a primary total ankle arthroplasty, and implants designed for primary arthroplasty can be used in most patients managed with conversion to total ankle replacement. STEP 2: PATIENT POSITIONING: Position the patient as for a primary total ankle replacement. STEP 3: REMOVE HARDWARE AND INSERT PROPHYLACTIC MALLEOLAR SCREWS: Preserve exsanguination time by removing hardware prior to inflating the tourniquet. STEP 4: RECREATE THE TIBIOTALAR JOINT: Recreate the native joint line, which can be relatively easy in selected patients and challenging in others. STEP 5: SET THE OPTIMAL TALAR SLOPE: Set the optimal talar slope, which can be challenging, particularly when the ankle arthrodesis is malunited in equinus. STEP 6: RECREATE THE MEDIAL AND LATERAL GUTTERS: Because the former medial and lateral articulations between the talus and the malleoli can be difficult to define, use careful surgical technique to avoid compromise of the malleoli and excessive talar resection. STEP 7: MOBILIZE THE ANKLE AND USE BONE GRAFT IN DEFECTS FROM PREVIOUS HARDWARE: To avoid potential malleolar fractures, mobilize the ankle only after the prophylactic malleolar screws have been placed; the tibial and talar cuts, completed; the gutters, reestablished; all resected bone, removed; and scar tissue from the posterior aspect of the ankle, excised; thereafter, conversion total ankle arthroplasty is similar to a primary total ankle replacement, with the exception of potential bone defects where prior hardware was positioned. STEP 8: TALAR PREPARATION: Perform the routine steps for primary total ankle arthroplasty, often ignoring bone defects from the ankle arthrodesis hardware, but plan to repair the defects with bone-grafting before implanting the final talar component. STEP 9: TIBIAL PREPARATION AND DEFINITIVE COMPONENTS: Perform tibial preparation in a manner similar to that used for primary total ankle arthroplasty. RESULTS: We performed 23 conversion total ankle arthroplasties in patients who had an ankle arthrodesis, including those with pain despite successful fusion and those with painful nonunions(9). PITFALLS & CHALLENGES: